Computational methods of missile aerodynamics - Atta, E. H. (2008)
A computational method has been developed for the prediction of missile flow fields with emphasis on subsonic and transonic flight-conditions. The computational method is based on the thin shear layer formulation of the Navier-Stokes equations and a finite volume Runge-Kutta time marching algorithm.